2018
DOI: 10.12968/ijtr.2018.25.7.353
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and barriers of adherence to home exercise programmes after stroke: caregiver perceptions

Abstract: Background/Aims: In stroke rehabilitation, the goal is to discharge patients at their optimal functional level, however, this level of independence is not always reached at discharge due to decreased length of stay and a high demand for beds. Thus, patients rely upon caregivers to assist them not only with activities of daily living but also with home exercise programmes. The purpose of this study was to establish caregivers' perceived enablers and barriers of adherence to home exercise programmes in stroke su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Dose and content of UL HEP are variable, ranging from a structured one-size-fits-all program, to an individualised program specific to the needs and goals of the stroke survivor [ 6 ]. Adherence to HEP after stroke has been attributed to family support, confidence in therapist knowledge and experience, and goal oriented practice with an accountability strategy [ 7 – 9 ]. Non-adherence with HEP after stroke has been attributed to fatigue, depression and diminished motivation, musculoskeletal issues, and lack of time due to competing commitments [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose and content of UL HEP are variable, ranging from a structured one-size-fits-all program, to an individualised program specific to the needs and goals of the stroke survivor [ 6 ]. Adherence to HEP after stroke has been attributed to family support, confidence in therapist knowledge and experience, and goal oriented practice with an accountability strategy [ 7 – 9 ]. Non-adherence with HEP after stroke has been attributed to fatigue, depression and diminished motivation, musculoskeletal issues, and lack of time due to competing commitments [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to HEP after stroke has been attributed to family support, confidence in therapist knowledge and experience, and goal oriented practice with an accountability strategy [ 7 – 9 ]. Non-adherence with HEP after stroke has been attributed to fatigue, depression and diminished motivation, musculoskeletal issues, and lack of time due to competing commitments [ 8 , 9 ]. Additionally, some stroke survivors have found that traditional HEP are not enjoyable, too difficult or insufficiently challenging, and thus of minimal functional benefit [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers have a lot of responsibilities and they experience emotional strain and burden. This may influence stroke survivors’ adherence to home exercise programmes and recovery of function as some of them rely upon caregivers for assistance (Scorrano, Ntsiea & Maleka 2018). Thus, caregivers and stroke survivors need more support post-discharge.…”
Section: Resultsmentioning
confidence: 99%
“…However, fitness professionals report that they have limited confidence in supporting the specific needs of PwS (Condon & Guidon, 2018 ) and inaccessible equipment has been identified as a barrier to the uptake of exercise amongst the stroke population (Nicholson et al, 2014 ). Exercise programmes can be effectively delivered in the home environment (Galvin et al, 2014 ) but barriers to exercising at home include fear of falling, caregiver addressing other priorities, unsuitable environment and limited confidence with correct exercise technique (Galvin et al, 2014 ; Scorrano et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%